2021
DOI: 10.1007/s41130-021-00151-1
|View full text |Cite
|
Sign up to set email alerts
|

Does catch-and-release increase the recreational value of rivers? The case of salmon fishing

Abstract: Catch-and-release (C&R) could be an interesting management tool in recreational fisheries as long as mortality remains low and the anglers' well-being does not drop. We used a choice experiment to examine the potential of C&R angling as a monitoring tool for the salmon recreational fishery in Brittany (France) in summer 2017. Anglers were asked to choose between hypothetical fishing day trips differing in terms of their combination of relevant attributes and levels and distance to travel. From the analysis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 45 publications
(58 reference statements)
0
4
0
Order By: Relevance
“…A relevant question then is whether a reasonable high level of angler satisfaction, defined as the reward recreational anglers receive from their fishing experience (Birdsong et al 2021), can be achieved without actually harvesting the fish. Indeed, some studies have suggested that some angler groups receive satisfaction from voluntarily releasing their catch (Ditton and Sutton 2004;Liu et al 2019;Ropars-Collet et al 2021), although the benefits of releasing fish are lower than the benefits of retained fish in consumptive fisheries (Lee et al 2017). Indeed, in salmonid fisheries, harvesting fish can be of very high value (Olaussen and Skonhoft 2008;Olaussen 2016;Ropars-Collet et al 2021), but strong heterogeneity exists as to whether salmonid anglers prefer to catch or release fish (Hutt and Bettoli 2007).…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…A relevant question then is whether a reasonable high level of angler satisfaction, defined as the reward recreational anglers receive from their fishing experience (Birdsong et al 2021), can be achieved without actually harvesting the fish. Indeed, some studies have suggested that some angler groups receive satisfaction from voluntarily releasing their catch (Ditton and Sutton 2004;Liu et al 2019;Ropars-Collet et al 2021), although the benefits of releasing fish are lower than the benefits of retained fish in consumptive fisheries (Lee et al 2017). Indeed, in salmonid fisheries, harvesting fish can be of very high value (Olaussen and Skonhoft 2008;Olaussen 2016;Ropars-Collet et al 2021), but strong heterogeneity exists as to whether salmonid anglers prefer to catch or release fish (Hutt and Bettoli 2007).…”
mentioning
confidence: 99%
“…Indeed, some studies have suggested that some angler groups receive satisfaction from voluntarily releasing their catch (Ditton and Sutton 2004;Liu et al 2019;Ropars-Collet et al 2021), although the benefits of releasing fish are lower than the benefits of retained fish in consumptive fisheries (Lee et al 2017). Indeed, in salmonid fisheries, harvesting fish can be of very high value (Olaussen and Skonhoft 2008;Olaussen 2016;Ropars-Collet et al 2021), but strong heterogeneity exists as to whether salmonid anglers prefer to catch or release fish (Hutt and Bettoli 2007). A recent study by Gundelund et al (2022) from Danish sea trout angling revealed that the satisfaction of anglers increased with the catch rate of sea trout, but primary motivations of anglers moderated how strongly catch contributed to angler satisfaction.…”
mentioning
confidence: 99%
See 2 more Smart Citations